Pediatric emergency department; resource exhaustion and burden of work in a resource-constrained region.: Pediatric Emergency Department in Baghdad - Ghali, Hasanein Habeeb; Al-Shafiei, Mustafa A.; Al-Musawi, Hayder M. (Journal of the Faculty of Medicine Baghdad, 2021)
Background: emergency care is well known as the care delivered in a hospital setting to any patient with unexpected, sudden, threatening reversible condition. In countries where health care is not optimum, this type of care represents the weakest element of the health system. Aims of the study: to figure out the main causes behind the admission in Pediatric Emergency Department (PED) of Children Welfare Teaching Hospital (CWTH) and the urgency of visits. Patients and methods: a cross sectional study retrospective analysis that was carried out in the PED of CWTH in Medical City, Baghdad. Five hundred visits for patients below the age of 14 years between August and November 2017 were enrolled in this study and their data were analyzed. Perceived urgency of the current visit was assessed and analyzed. Results: the mean age for the patients was 3 years. Males represent 239 patients (47.8%). Of the whole group, 110 patients with a range of hours (22.0%). The most common complaint recorded was fever in 175 patients (21.0%). The most common comorbidities recorded were chronic respiratory diseases in 10 patients. Complete blood count was ordered for 460 patients (92.0%). Strikingly, blood culture was recorded in 5 patients only (1.0%). Reviewing the patients’ files has shown that 381 patients (76.2%) were prescribed antibiotics during stay in PED. The diagnosis of the patients visiting the PED was documented in 252 (50.4%) patients’ files only. Lower respiratory tract infections were the most frequently recorded diagnosis in 41 patients (8.2%). 266 patients (53.2%) were shown to be urgent visits, while 234 of them (46.8%) were non-urgent visits. Most of the patients who have comorbidities were labeled as urgent patients (89.4%), with a significant statistical difference (P value 0.001). Most of the patients who presented with a duration of complaint of within hours (89.1%) were stratified as urgent cases. Noteworthy, the majority of the patients who did not receive antibiotic therapy were stratified to be urgent (74.7%), the p value was 0.0001. Considering the disposition of the patients, majority of the patient who were discharged home (61.2%) were stratified as non-urgent, while (38.8%) were urgent. Conclusions: The study identifies the critical pitfalls of improper documentation of the data in the PED. It also delineates the resource exhaustion from the non-urgent visits. This may call for the need of structured training of physicians in the PED to improve efficiency, and reduce the cost and expenses of each patients through reducing the investigations and this will improve the standards of service. Triage system should be implemented in CWTH PED.